Flatlands in the Holy Land: The Evolution of Layered Materials Research in Israel. Issue 41 (16th May 2018) - Hod, Oded; Urbakh, Michael; Naveh, Doron; Bar‐Sadan, Maya; Ismach, Ariel
Abstract: The experimental identification of fullerenes in 1985, carbon nanotubes in 1991, inorganic nanotubes in 1992, and graphene in 2004 are cornerstone events that have marked the beginning of the layered nanostructures era of materials science. Nowadays, the synthesis of such low‐dimensional systems is a routine practice allowing the controlled fabrication of 0‐, 1‐, and 2D layered structures of diverse chemical compositions. These systems possess unique physical properties that stem from their structural anisotropy characterized by strong intralayer covalent bonding and weaker interlayer dispersive interactions. This, in turn, results in promising functionality that attracts the attention of scientists from many disciplines including chemists, physicists, material scientists, engineers, as well as life scientists that are interested in both their basic and applied science aspects. Here, a short review of the contribution of the Israeli scientific community to this effort over the past 3 decades, is provided. Abstract : Low‐dimensional layered materials have been in the forefront of materials science research over the past few decades due to their unique physical properties and potential applications. The degree of success in their integration into novel technologies strongly depends on future scientific breakthroughs in this field. A brief review of the research of these unique nanomaterials is provided, focusing on significant contributions made by the Israeli scientific community.